Current advances in screening for bioactive components from medicinal plants by affinity ultrafiltration mass spectrometry. Issue 4 (21st May 2018) - Chen, Guilin; Huang, Bill X.; Guo, Mingquan
Abstract: Introduction: Medicinal plants have played an important role in maintaining human health for thousands of years. However, the interactions between the active components in medicinal plants and some certain biological targets during a disease are still unclear in most cases. Objective: To conduct the high‐throughput screening for small active molecules that can interact with biological targets, which is of great theoretical significance and practical value. Methodology: The ultrafiltration mass spectrometry (UF‐LC/MS) is a powerful bio‐analytical method by combining affinity ultrafiltration and liquid chromatography‐mass spectrometry (LC/MS), which could rapidly screen and identify small active molecules that bind to biological targets of interest at the same time. Compared with other analytical methods, affinity UF‐LC/MS has the characteristics of fast, sensitive and high throughput, and is especially suitable for the complicated extracts of medicinal plants. Results: In this review, the basic principle, characteristics and some most recent challenges in UF‐LC/MS have been demonstrated. Meanwhile, the progress and applications of affinity UF‐LC/MS in the discovery of the active components from natural medicinal plants and the interactions between small molecules and biological target proteins are also briefly summarised. In addition, the future directions for UF‐LC/MS are also prospected. Conclusion: Affinity UF‐LC/MS is a powerful tool in studies on the interactions between small active molecules and biological protein targets, especially in the high‐throughput screening of active components from the natural medicinal plants. Abstract : The most recent development of UF‐MS, and its applications in the identification of targeted bioactive components from medicinal plants have been reviewed. As a highly selective method for bio‐affinity capture and high through‐put screening, UF‐MS is very useful not only for screening of bioactive molecules, but also for the evaluation of the quality, and efficacy of medicinal plants.